Development and evaluation of the perceived variety-support in physical education scale (PVSPES). Issue 21 (2nd November 2022) - Eather, N.; McLachlan, E.; Sylvester, B. D.; Diallo, T.; Beauchamp, M.R.; Lubans, D.R.
ABSTRACT: The provision of variety has been posited to influence motivation in physical education. Therefore, the aim of this 3-phase study was to design and evaluate a brief scale to assess ratings of variety-support in physical education. In Phase 1, 20 experts were invited to review the developed items of the Perceived Variety-Support in Physical Education (PVSPE) scale. In Phase 2, factorial validity of item responses was assessed in a sample of adolescents aged 12–14 years (n = 265). In Phase 3, test-retest reliability was determined over a one-week period (n = 100). A one-factor model resulted in "good" fit to the data (χ2(21) = 43.265, p < 0.001, CFI = 0.968, TLI = 0.952, RMSEA = 0.089; factor loading estimates showed that indicators were highly related to the factor (range: 0.60 to 0.93); and ICC was 0.98, 95% CI [0.97 to 0.98]. Our results provide initial evidence for the validity, measurement invariance, and test-retest reliability of scores derived from the VSPE scale for use with adolescents.